Projected estimates of cancer in Canada in 2022 - Brenner, Darren R.; Poirier, Abbey; Woods, Ryan R.; Ellison, Larry F.; Billette, Jean-Michel; Demers, Alain A.; Zhang, Shary Xinyu; Yao, Chunhe; Finley, Christian; Fitzgerald, Natalie; Saint-Jacques, Nathalie; Shack, Lorraine; et al. (Canadian Medical Association journal (CMAJ), 2022)
Regular cancer surveillance is crucial for understanding where progress is being made and where more must be done. We sought to provide an overview of the expected burden of cancer in Canada in 2022. We obtained data on new cancer incidence from the National Cancer Incidence Reporting System (1984–1991) and Canadian Cancer Registry (1992–2018). Mortality data (1984–2019) were obtained from the Canadian Vital Statistics — Death Database. We projected cancer incidence and mortality counts and rates to 2022 for 22 cancer types by sex and province or territory. Rates were age standardized to the 2011 Canadian standard population. An estimated 233 900 new cancer cases and 85 100 cancer deaths are expected in Canada in 2022. We expect the most commonly diagnosed cancers to be lung overall (30 000), breast in females (28 600) and prostate in males (24 600). We also expect lung cancer to be the leading cause of cancer death, accounting for 24.3% of all cancer deaths, followed by colorectal (11.0%), pancreatic (6.7%) and breast cancers (6.5%). Incidence and mortality rates are generally expected to be higher in the eastern provinces of Canada than the western provinces. Although overall cancer rates are declining, the number of cases and deaths continues to climb, owing to population growth and the aging population. The projected high burden of lung cancer indicates a need for increased tobacco control and improvements in early detection and treatment. Success in breast and colorectal cancer screening and treatment likely account for the continued decline in their burden. The limited progress in early detection and new treatments for pancreatic cancer explains why it is expected to be the third leading cause of cancer death in Canada.